Rationale, Design, and Methods for Nen Unkumbi/Edahiyedo (“We Are Here Now”): A Multi-Level Randomized Controlled Trial to Improve Sexual and Reproductive Health Outcomes in a Northern Plains American Indian Reservation Community - Rink, Elizabeth; Firemoon, Paula; Anastario, Michael; Johnson, Olivia; GrowingThunder, Ramey; Ricker, Adriann; Peterson, Malory; Baldwin, Julie (Frontiers in Public Health, 2022)
American Indian (AI) youth in the United States experience disproportionate sexual and reproductive health (SRH) disparities relative to their non-Indigenous, white counterparts, including increased rates of sexually transmitted infections (STIs), earlier sexual debut, increased rates of teen birth, and reduced access to SRH services. Past research shows that to improve SRH outcomes for AI youth in reservation communities, interventions must address complex factors and multiple levels of community that influence sexual risk behaviors. Here, we describe development of a multi-level, multi-component randomized controlled trial (RCT) to intervene upon SRH outcomes in a Northern Plains American Indian reservation community. Our intervention is rooted in a community based participatory research framework and is evaluated with a stepped wedge design that integrates 5 reservation high schools into a 5-year, cluster-randomized RCT. Ecological Systems Theory was used to design the intervention that includes 1) an individual level component of culturally specific SRH curriculum in school, 2) a parental component of education to improve parent-child communication about SRH and healthy relationships, 3) a community component of cultural mentorship, and 4) a systems-level component to improve delivery of SRH services from reservation healthcare agencies. In this article we present the rationale and details of our research design, instrumentation, data collection protocol, analytical methods, and community participation in the intervention. Our intervention builds upon existing community strengths and integrates traditional Indigenous knowledge and values with current public health knowledge to reduce SRH disparities.